2010
DOI: 10.1210/en.2009-1435
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Expression of Thyroid Hormone-Responsive Spot 14 Protein Is Regulated by Constitutive Androstane Receptor (NR1I3)

Abstract: The pregnane X receptors (PXRs) and the constitutive androstane receptor (CAR) were initially isolated as nuclear receptors regulating xenobiotic metabolism and elimination, alleviating chemical insults. However, recent works suggest that these xenoreceptors play an endobiotic role in modulating hepatic lipid metabolism. In this study, we show that CAR activators]phenobarbital and 6-(4-chlorophenyl)imidazo[2,1-b][1,3]thiazole-5-carbaldehyde O-(3,4-dichlorobenzyl)oxime] induce the lipogenic gene thyroid hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…In vitro data from the hepatic Huh7 cell line and cryopreserved small hepatocytes have shown that TH may regulate the expression of specific CAR target genes possibly by binding of the activated TH receptor to the PBREM region (Ooe et al 2009, Bing et al 2014. In addition, it was shown that CAR itself can regulate the TH responsive gene Thrsp through binding to TRE sequences of the promoter region (Breuker et al 2010). Since xenobiotics are known to exert strong influence on TH metabolism, it is important to consider that activation of CAR by 3,5-T 2 might alter hepatic TH homeostasis via secondary mechanisms through induced liver DME synthesis and enhanced TH clearance (Maglich et al 2004, Qatanani et al 2005, Radovic et al 2010, Roques et al 2013, Schraplau et al 2014.…”
Section: -T 2 Alters Murine Genesmentioning
confidence: 99%
“…In vitro data from the hepatic Huh7 cell line and cryopreserved small hepatocytes have shown that TH may regulate the expression of specific CAR target genes possibly by binding of the activated TH receptor to the PBREM region (Ooe et al 2009, Bing et al 2014. In addition, it was shown that CAR itself can regulate the TH responsive gene Thrsp through binding to TRE sequences of the promoter region (Breuker et al 2010). Since xenobiotics are known to exert strong influence on TH metabolism, it is important to consider that activation of CAR by 3,5-T 2 might alter hepatic TH homeostasis via secondary mechanisms through induced liver DME synthesis and enhanced TH clearance (Maglich et al 2004, Qatanani et al 2005, Radovic et al 2010, Roques et al 2013, Schraplau et al 2014.…”
Section: -T 2 Alters Murine Genesmentioning
confidence: 99%
“…In agreement with morphologic observations, overexpression of ADFP, PLIN4, SCD1, LPIN1 was not prevented by cotreatment with either cytokine, suggesting that an inflammation stress does not affect induction of phospholipidosis by CPZ. It is noteworthy that expression of the PXR/ CAR target gene THRSP was down-regulated by cytokines, especially IL-6, as a consequence of their ability to down-regulate these nuclear receptors (Breuker et al, 2010). At 50 mM, CPZ was found to generate an early oxidative stress, which was associated with an inhibition of TA efflux, and shortly later, of its uptake, and alterations of bile canaliculi structures (Antherieu et al, 2013).…”
Section: Impact Of Inflammation On Chlorpromazine Hepatotoxicity 1563mentioning
confidence: 99%
“…The messenger RNA expression of THRSP was highly correlated with intramuscular fat content of an individual in Wagyu × Hereford cattle (Wang et al 2009). Research showed that the THRSP gene has impact on chicken fat metabolism (Breuker et al 2010) and SNPs could be used in molecular marker assistant selection (MAS) as a genetic marker for the chicken and pig growth traits (Wang et al 2004, d'Andre Hirwa et al 2010. However, up to now, the research about SNPs of the THRSP gene was not reported in goat.…”
Section: Introductionmentioning
confidence: 99%